Worcestershire Regiment in the Great War. - Stacke, Fitz M. (Worcestershire Regiment in the Great War., 2013)
Arguably the finest regimental history even written. A magnificent publication it is with its profusion of maps, illustrations and photos - each page of photos contains several. The Worcesters was one of the five regiments that had four regular battalions before the war, with two special reserve and two territorial battalions. By the end of the war another fourteen battalions had been raised for a total of twenty-two of which twelve went on active service. 9,460 officers and men gave their l ...